Cross-modal serial dependence in visual and auditory perception - Sim, Jia Yi (2018)
This paper investigated the effect of perceptual history on our present perception of stimuli across the visual and auditory modalities, particularly for pitch and height. With vast amounts of information to process from our environment, our perceptual systems rely on associations and biases to reduce perceptual processing load. Associations, such the cross-modal correspondence between pitch and height, have been theorized to facilitate multisensory integration and play a significant role in helping us perceive our environment. Also, perceptual aftereffects are biases that help maintain a stable perception of our surroundings; one of the positive aftereffects being serial dependence, where past stimuli influence our perception of the present. Serial dependence was not observed between pitch and height, as the auditory and visual systems may have inherent differences, and the methods used may have introduced artefacts and biases in the data collected. Future studies may modify the response scale used and look at physical constructs to investigate the presence of serial dependence across modalities.